Jesus’s Solidarity with Human Mortality and Perfection of Sonship in the Epistle to the Hebrews - Lee, Jihye (2024)
In relation to the discussion on the concept of perfection in Hebrews, the author’s emphasis on Jesus’s solidarity with human mortality has been considered as simple reference to the precondition of his Christological role and his sympathetic character, which shares human weaknesses. However, the substantial connection between the discussions on sonship in Heb 12 and on the Son in Heb 1–2 suggests a fresh reading of the text’s emphasis on Jesus’s mortality along with his role as ἀρχηγός of other sons. The author of Hebrews presents the notion that human mortality is a divinely designed opportunity for the sons of God to acquire the discipline necessary to be prepared to become the heirs of the eternal inheritance. The one who totally entrusts his own life to the Father is the genuinely obedient son, and this true obedience is cultivated when the sons choose obedience on the occasion of the test, i.e., “fear of death,” which is unaffectedly derived from the status of mortality.
Keywords: Discipline; forerunner; Perfection; Sonship; human mortality